Performance of GFRP sheets in strengthening concrete beams in flexure - Sakhiah Abdul Kudus; Siti Hajar Aisyah Mohd Din; M. S. Haji Sheik Mohammed; V. Roopa; Zakiah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Plain concrete beam repair and strengthening are increasingly important in structural strengthening and retrofitting. This study examines the glass fibre-reinforced polymer (GFRP) sheets in plain concrete beams under flexural behaviour by using its patching sheets. Through the implementation of a symmetrical four-point static loading technique, a series of tests were conducted on plain concrete beams that had been externally joined with GFRP sheets. These beams were subjected to rigorous testing until they reached their ultimate failure point. The experimental test consists of casting nine plain concrete beams with identical specifications. Three beams are utilised as control beams; three are reinforced with GFRP sheets measuring 50 mm × 100 mm, and another three are reinforced with GFRP sheets measuring 100 mm × 200 mm. The flexural test is designed to determine the tensile strength of concrete under bending. Compared to the control beams, the specimens strengthened with GFRP sheets demonstrated a significantly enhanced ultimate load capacity. The beams with larger GFRP sheets exhibited a higher ultimate load of 14.84 kN, while those with smaller sheets showed an ultimate load of 8.54 kN, marking an appreciable improvement in performance. Moreover, the smaller area GFRP-reinforced beams failed at a 45% higher shear stress compared to those with a larger area GFRP, indicating a differential impact based on the size of the reinforcement used. This study highlights the effectiveness of GFRP sheets in enhancing the structural performance of plain concrete beams, providing crucial insights into the benefits of different sizes of reinforcement.